Penerapan Teknik Scuba Diving Terhadap Penurunan Resiko Penyakit Dekompresi Pada Penyelam Tradisional di Pulau Bungin - Ashari , Imam; Imansyah, Yadi; Evitamala, Lilik (Jurnal Porkes, 2025)
This study is motivated by the high rate of decompression sickness in traditional divers on bungin island who have difficulty recovering. the problem in this study is “the application of scuba diving techniques to reduce the risk of decompression sickness in traditional divers on Bungin Island”. This study aims to determine whether or not there is an effect of applying scuba diving techniques on reducing the risk of decompression sickness. this research is an experimental study. This study uses two variables consisting of one independent variable (application of scuba diving techniques) and one dependent variable, namely (decreased risk of decompression sickness). The population used in this study were traditional divers who were included in the inclusion and exclusion criteria, totaling 24 divers. The sampling technique used is porposive sampling technique. Data collection techniques using pretest and posttest methods. The data analysis technique uses t test analysis with a significant level of 5%. Because t count is 22.73 which is compared with t table at a significant level of 5% at degrees of freedom n-1 (24-1 = 23) which is 1.714. Because t count > t table (22.73 > 1.714), the working hypothesis is accepted so it can be concluded that this study has an effect on the application of scuba diving techniques to reduce the risk of decompression sickness in traditional divers on Bungin Island.